Strategic analysis of the company Regiojet a.s. - Danišková, Alexandra; Pernica, Karel; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The goal of this bachelor thesis is to provide strategic recommendations for the management of the company RegioJet a.s. lead by Radim Jančura. The thesis is divided into two main parts – theoretical and practical. In the theoretical part, the tools used for strategic analysis will be described and explained. Furthermore, the company will be analyzed using these strategic analysis tools such as PEST, five Porter forces analysis, VRIO analysis, Performance analysis, and Scenario planning. For the analysis, both qualitative and quantitative data were used to paint an accurate picture of the company’s strengths, weaknesses, opportunities, and threats. The analysis will be connected and summarized in the SWOT analysis from which the strategic recommendations will arise.
Vedoucí práce: Karel Pernica
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses